A arte rupestre como expressão comunicativa da cultura - Alves, Gerlúzia de Oliveira Azevedo (2006)
Along their existence, through of the millenniuns, the Man registers, one way or another, their saga. One in those registration ways is the rupestrian art. Through the rupestrian art the Prehistory is brought even us, portraying in images the daily ritualist and magic of the Man, in scenes that show, among other, their cults and also their daily hard work. The Man is imposed, while registering of their existence, starting from the moment in that he is capable to leave their marks through the transformation that attributes to the Nature; also for the produced interferences and for the cultural singularities that themselves were constituted before the period of the alphabetical writing. In an artifice of duplicating utensils and in the sense of representing animals and to himself own, he delegated us a communicative system whose contexts and details were - and it continue being - an enigma to be deciphered. Starting from this argument, the research has for objective to understand the daily and the history of cultural groups that they preceded us, taking as base the reading of the rupestrian paintings found at the located archeological ranches in the Area of Seridó, more specifically in the Complexo Xique-xique, close to the Municipal district of Carnaúba dos Dantas, distant 220 kilometers of Natal, the capital of Rio Grande do Norte State